The Influence of Resistance to Change on Public-Sector Reform Implementation: The Case of Italian Municipalities' Internal Control System. Issue 12 (14th October 2016) - Reginato, Elisabetta; Fadda, Isabella; Paglietti, Paola
ABSTRACT: The present research tries to contribute to the academic debate on public management reform adoption, focusing on the reasons for the discrepancies between actual and formal changes and using resistance to change as theoretical basis. The study hypothesizes that high levels of individual and organizational resistance to change may be associated to the formal implementation of public management reforms. The research results allow to confirm the hypothesis when large-size municipalities are considered, while when considering medium-size entities a definite evidence of a relation between resistance to change and the formal implementation of the reforms does not emerge.